Design and Development of Ion Probe Testing on Four Stroke Engine Model - Ng, Noveen Nico Alexandra; A. A. A., Ahmad Shamsuddin; M. M., Hasin; N. S., Mazlan; M. L., Mohd Isnin (2016)
This paper carried out the study on an ion probe testing on four stroke engine model. The testing probe was installed inside the engine combustion chamber with specific distance, when the fuel is supply to the engine and the spark plug light up the fuel, it will produce an ionization flame, at the same time, when the flame touch the probe, it will generate a signal. The probe is connected to a circuit, when the signal is generated, the circuit will process the signal. The coding for the process is written inside a chip that installed in the circuit. A user interface was created to display the result. Besides that, a camera will use to catch the flame to compare with the result.